Kajian Strukturalisme Puisi “Ujung-Ujung Hujan” Karya Aan Mansyur (Jurnal Sosial Humaniora dan Pendidikan, 2023)
This study uses the object of the literary work of poetry "Surat Dari Ibu", by Asrul Sani by using structuralism studies. The purpose of this study is to describe the physical elements and mental elements as a whole which allows to provide new knowledge to the reader. This study uses a qualitative approach to the method of content analysis in poetry. The results obtained in the physical structure of the poem are 2 diction related to the selection of words used by the poet. Imagery found 3 images related to the human sensory organs. There are 3 concrete words related to the meaning of the word as a whole. There is 1 style of language, namely comparative majas. Rhyme uses aabb rhyme. The last physical element is typography, the poet uses all lowercase typography in his poem. The inner elements contained in the poem "Ujung-Ujung Hujan" by Aan Mansyur, the first is the theme found in one stanza related to the problems in the poem. Based on tone, 1 tone was found. The inner element of flavor is found to be a sense of nostalgia and sadness of someone in the poem "Ujung-Ujung Hujan" by Aan Mansyur. The last inner element is the mandate, there is one mandate that the poet wants to convey through his poem.